A review of the upper Campanian vertebrate site of Armuña (Segovia Province, Spain). (January 2016) - Pérez-García, A.; Ortega, F.; Bolet, A.; Escaso, F.; Houssaye, A.; Martínez-Salanova, J.; de Miguel Chaves, C.; Mocho, P.; Narváez, I.; Segura, M.; Torices, A.; Vidal, D.; et al.
Abstract: The Upper Cretaceous outcrops of Armuña (Segovia Province, Spain) yielded relatively abundant material of vertebrates during prospection and excavation in the second half of the 1980s. However, little has been published on these remains. A new analysis of the specimens from this upper Campanian site reveals the presence of some clades in the site for the first time (e.g., Dortokidae, Anguimorpha, Mosasauroidea). Furthermore, the material of the clades previously recognized there has been reviewed and described in more detail, with some previous systematic attributions confirmed and others refuted. Consequently, a relatively high local diversity has been identified. New taxa (i.e., a member of Anguimorpha and a eusuchian crocodyliform) are identified in Armuña, coexisting with other taxa previously described in other sites from the Iberoarmorican Realm. The vertebrates from Armuña confirm that the fauna from the Upper Cretaceous of the Iberian Peninsula is composed of a mixture of European endemic clades and lineages shared with other continents such as North America (e.g., anguimorphs) and Africa (e.g., bothremydids). Highlights: The vertebrate taxa from Armuña are studied here. This upper Campanian site is situated in the Segovia Province (Central Spain). A relatively high abundance and diversity of reptiles is recognized there. New taxa, and forms previously known in the Iberoarmorican Realm, are identified. European clades and lineages that migrated from other continents are present there.